2016
DOI: 10.1002/cphc.201600499
|View full text |Cite
|
Sign up to set email alerts
|

Graphene‐Coated ZnO and SiO2 as Supports for CoO Nanoparticles with Enhanced Reducibility

Abstract: The insertion of a graphene layer between cobalt and a substrate modifies the morphology and the oxidation/reduction properties of supported cobalt particles. Co forms a relatively flat structure on ZnO and SiO , whereas individual Co nanoparticles are formed after graphene coating of these substrates. The graphene layer moderates the formation of cobalt oxide in 5×10 mbar O and promotes the reduction of oxidized Co in H at lower temperature. Angle-resolved XPS measurements indicate that this is mainly a conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…As shown by the Co 2p 3/2 XPS spectra in Figure , after annealing under UHV conditions cobalt supported on graphene‐coated ZnO could maintain the metallic state till 350 °C (Figure b). Contrarily, without the graphene layer Co was readily oxidized to CoO (Figure a) presumably through a solid state interface interaction with the ZnO support, as indicated later by angle‐resolved XPS spectra . In a more recent study, it was shown that graphene layer also weakens the interactions between Co and SiO 2 , even if SiO 2 is considered as a relatively inert substrate as compared to ZnO .…”
Section: Graphene‐coated Metal Oxides In Catalytic Applicationsmentioning
confidence: 88%
See 4 more Smart Citations
“…As shown by the Co 2p 3/2 XPS spectra in Figure , after annealing under UHV conditions cobalt supported on graphene‐coated ZnO could maintain the metallic state till 350 °C (Figure b). Contrarily, without the graphene layer Co was readily oxidized to CoO (Figure a) presumably through a solid state interface interaction with the ZnO support, as indicated later by angle‐resolved XPS spectra . In a more recent study, it was shown that graphene layer also weakens the interactions between Co and SiO 2 , even if SiO 2 is considered as a relatively inert substrate as compared to ZnO .…”
Section: Graphene‐coated Metal Oxides In Catalytic Applicationsmentioning
confidence: 88%
“…Contrarily, without the graphene layer Co was readily oxidized to CoO (Figure a) presumably through a solid state interface interaction with the ZnO support, as indicated later by angle‐resolved XPS spectra . In a more recent study, it was shown that graphene layer also weakens the interactions between Co and SiO 2 , even if SiO 2 is considered as a relatively inert substrate as compared to ZnO . Moreover, the interaction between Co and graphene dictates not only the oxidation state but also the particles size of cobalt.…”
Section: Graphene‐coated Metal Oxides In Catalytic Applicationsmentioning
confidence: 89%
See 3 more Smart Citations